Legal Certainty Special Mining Business License (Study: IUPK as a Continuation of Contract of Work and Work Agreement for Coal Mining Exploitation in the Minerba Law) - Riyadi, Panji (Budapest International Research and Critics University, 2021)
After the promulgation of Law Number 3 of 2020 many people highlighted the addition of Article 169A which explains the guarantee of extension through special mining business license (IUPK) for holders of the contract of work (KK) and work agreement for coal mining exploitation (PKP2B) which will expire. However on the other hand this Article also creates unrest for KK and PKP2B holders because the granting of extensions through the IUPK is not automatically granted but with considerations that have been explained in the law. The formulation of the problem raised in this study is about the legal certainty of granting IUPK and legal protection for KK and PKP2B holders if the application for extension through IUPK is rejected by the Ministry of Energy and Mineral Resources. This study uses a normative juridical research method namely through a literature study with a statutory approach. The results indicate that there was no legal certainty from the IUPK as a Continuation of Contract/Agreement Operations and no legal protection for KK and PKP2B holders if the extension through IUPK is rejected by the relevant Minister. The provisions regarding these rules in the current Minerba Law must be explained more clearly in the Government Regulation regarding Minerba in order to provide legal certainty and protection for mining business actors.